Musical Creation “Jegong” | Tabuh Kreasi “Jegong” - krisna Adinata I Putu Gede; Sujayathi Ni Wayan Masyuni (GHURNITA: Jurnal Seni Karawitan, 2023)
Building a work of art certainly goes through a lot of processes and stages, in this case an artist or a composer who explores several phenomena. Seeing this phenomenon, the stylists were motivated to create works that used ideas from a Balinese gamelan stylist's life experience of combining/collaborating both elements of Jegog gamelan and Gong Kebyar gamelan. In the form of depictions of gending, namely the life experience of playing gamelan and containing the structures, motifs and techniques of the two gamelans which are used as a form of percussion creations entitled Jegong. The purpose of making this work is to offer a new nuance to the Jegog gamelan in collaboration with the Gong Kebyar gamelan and to train arrangers to show their identity as potential composers in composing Balinese karawitan music. This Jegong work uses a method of creating works of art that uses the chopped pangi structure where this structure is used to create a composition work of Jegog stems in Jembrana Regency. To get the maximum artistic output, the stylist tries to convey Gong Kebyar playing in his own way and Jegog playing in his own way which is the focal point of the work made by the stylist to become innovative, creative and traditional ideas.